2008
DOI: 10.1152/japplphysiol.00323.2007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ischemic tolerance induced by hyperbaric oxygen preconditioning involves upregulation of hypoxia-inducible factor-1α and erythropoietin in rats

Abstract: We studied the effect of hyperbaric oxygen (HBO) preconditioning on the molecular mechanisms of neuroprotection in a rat focal cerebral ischemic model. Seventy-two male Sprague-Dawley rats were pretreated with HBO (100% O(2), 2 atmospheres absolute, 1 h once every other day for 5 sessions) or with room air. In experiment 1, HBO-preconditioned rats and matched room air controls were subjected to focal cerebral ischemia or sham surgery. Postinjury motor parameters and infarction volumes of HBO-preconditioned rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 50 publications
3
67
1
5
Order By: Relevance
“…In this IPC model, the activity of the antioxidant enzymes glutathione peroxidase, glutathione reductase, and Mn superoxide dismutase were significantly increased, whereas superoxide and hydrogen peroxide concentrations following OGD were significantly lower in the IPC group. Furthermore, cytochrome c release from mitochondria to the cytosol was suppressed in the ischemia tolerance-induced hippocampal CA1 region [65] Recent reports suggested that one mechanism of preconditioning probably involves hypoxia-inducible factor-1alpha (HIF1alpha) [66,67] . HIF-1alpha is a transcription factor that binds with a second protein (HIF-1beta) in the nucleus to promote elements in hypoxia-responsive target genes during hypoxia.…”
Section: Heat Shock Proteins (Hsps)mentioning
confidence: 99%
“…In this IPC model, the activity of the antioxidant enzymes glutathione peroxidase, glutathione reductase, and Mn superoxide dismutase were significantly increased, whereas superoxide and hydrogen peroxide concentrations following OGD were significantly lower in the IPC group. Furthermore, cytochrome c release from mitochondria to the cytosol was suppressed in the ischemia tolerance-induced hippocampal CA1 region [65] Recent reports suggested that one mechanism of preconditioning probably involves hypoxia-inducible factor-1alpha (HIF1alpha) [66,67] . HIF-1alpha is a transcription factor that binds with a second protein (HIF-1beta) in the nucleus to promote elements in hypoxia-responsive target genes during hypoxia.…”
Section: Heat Shock Proteins (Hsps)mentioning
confidence: 99%
“…Thus, the overall results prove the safety of long-term HBO treatments. More de tailed studies, including detections of the previously suggested molecules heme oxygenase-1 (25) and hypoxia inducible factor-a (37), warrant more precise knowledge in order to elucidate the underlying mechanisms of HBO-related oxidant/antioxidant interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of COX-2 expression by HBO 2 preconditioning provides protection in the rat model of transient global cerebral ischemia [106]. Gu et al [107] studied the effect of preconditioning on the molecular mechanisms of neuroprotection in a rat focal cerebral ischemic model. They found that ischemic tolerance induced by HBO 2 preconditioning involves upregulation of hypoxia-inducible factor-1alpha and erythropoietin in rats.…”
Section: Molecular Effects Of Hyperbaric Oxygen In Disorders and Expementioning
confidence: 99%
“…They found that ischemic tolerance induced by HBO 2 preconditioning involves upregulation of hypoxia-inducible factor-1alpha and erythropoietin in rats. This is interesting, since it resembles ischemic preconditioning where ischemic stimuli below the threshold of damage lead to ischemic tolerance [107], potentially suggesting that intermittent HBO 2 may represent signals perceived as a kind of pseudohypoxia. The decrease in the expression of the integrins LFA-1 and ICAM-1 is also a major mechanism for the protective effect of HBO 2 in ischemia-reperfusion injury [108].…”
Section: Molecular Effects Of Hyperbaric Oxygen In Disorders and Expementioning
confidence: 99%